2021
DOI: 10.21203/rs.3.rs-1189219/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 Omicron variant replication in human respiratory tract ex vivo

Abstract: Emergence of SARS-CoV-2 variants of concern (VOC) with progressively increased transmissibility between humans is a threat to global public health. Omicron variant also evades immunity from natural infection or vaccines1. It is unclear whether its exceptional transmissibility is due to immune evasion or inherent virological properties.We compared the replication competence and cellular tropism of the wild type (WT) virus, D614G, Alpha, Beta, Delta and Omicron variants in ex vivo explant cultures of human bronc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…However, these findings collectively suggest that differences in viral factors between the Omicron and the Delta variants, such as differences in viral tropism or virulence factors, might be driving the observed relative reductions in disease severity. Recent ex vivo studies demonstrate higher replication of the Omicron variant in the human upper respiratory tract as compared to the small airways of the lung [24], consistent with animal experiments suggesting that disease from infection with the Omicron variant might be confined to the large airway [25].…”
Section: Discussionsupporting
confidence: 63%
“…However, these findings collectively suggest that differences in viral factors between the Omicron and the Delta variants, such as differences in viral tropism or virulence factors, might be driving the observed relative reductions in disease severity. Recent ex vivo studies demonstrate higher replication of the Omicron variant in the human upper respiratory tract as compared to the small airways of the lung [24], consistent with animal experiments suggesting that disease from infection with the Omicron variant might be confined to the large airway [25].…”
Section: Discussionsupporting
confidence: 63%
“…While these results are consistent with the very preliminary clinical data in humans suggesting that B.1.1.529 causes a more transmissible yet possibly milder respiratory infection 40,41 , the basis for the attenuation in rodents remains unknown. One pre-print study suggests that B.1.1.529 replicates faster in the human bronchus and less in lung cells, which may explain its greater transmissibility and putative lower disease severity 42 ; although it remains unclear if these observations extend to rodents, we observed less infection of hamster bronchial cells in vivo with B.1.1.529 Omicron than B.1.617.2 Delta virus. We also measured lower viral burden in nasal washes and turbinates in 129 mice compared to other SARS-CoV-2 strains.…”
Section: Discussionmentioning
confidence: 52%
“…A team of researchers in Hong Kong compared the replication competency and cellular tropism of all Covid variants in ex vivo explant cultures of human bronchus and lung. They demonstrated that Omicron replicated more rapidly in the bronchus than any other SARS-CoV-2 strain but less e ciently in the lung parenchyma [20]. This nding might be a probable reason for reduced severity in Omicron infections.…”
Section: Discussionmentioning
confidence: 99%